2023
DOI: 10.1186/s12864-023-09610-z
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide identification and expression analysis of the Auxin-Response factor (ARF) gene family in Medicago sativa under abiotic stress

Fenqi Chen,
Jinqing Zhang,
Xue Ha
et al.

Abstract: Background Alfalfa (Medicago sativa) is the most widely planted legume forage and one of the most economically valuable crops in the world. The periodic changes in its growth and development and abiotic stress determine its yield and economic benefits. Auxin controls many aspects of alfalfa growth by regulating gene expression, including organ differentiation and stress response. Auxin response factors (ARF) are transcription factors that play an essential role in auxin signal transduction and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 65 publications
0
4
0
Order By: Relevance
“…Specifically, we observed an abundance of promoter elements related to the BHLH and bZIP families in multiple members of the MedARF16s subgroup, indicating that they might be regulated by downstream genes targeted by the BHLH and bZIP transcription factors [45], thereby exhibiting similar regulatory functions. They may co-regulate complex controlling the transcription of MedARFs and thereby influencing gene expression during the growth of M. dodecandrum [46].…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, we observed an abundance of promoter elements related to the BHLH and bZIP families in multiple members of the MedARF16s subgroup, indicating that they might be regulated by downstream genes targeted by the BHLH and bZIP transcription factors [45], thereby exhibiting similar regulatory functions. They may co-regulate complex controlling the transcription of MedARFs and thereby influencing gene expression during the growth of M. dodecandrum [46].…”
Section: Discussionmentioning
confidence: 99%
“…Duplication events, including tandem duplication and segmental/whole duplication, are the major forces for gene family expansion and functional differentiation during evolution. Previous studies have reported that plant ARF genes expand by undergoing tandem duplication and segmental/whole duplication ( Chen et al., 2023 ; Qi et al., 2023 ). For example, four LuARF genes (two gene pairs) underwent tandem duplication events, whereas 27 (81.8%, 18 gene pairs) underwent segmental/whole duplication events in flax ( Qi et al., 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…For example, four LuARF genes (two gene pairs) underwent tandem duplication events, whereas 27 (81.8%, 18 gene pairs) underwent segmental/whole duplication events in flax ( Qi et al., 2023 ). In alfalfa, 14 segmental duplications and two sets of tandem repeats were identified ( Chen et al., 2023 ). Similarly, seven CsARF genes (three sets of gene pairs) underwent tandem duplication, and one segmental duplication was identified ( Figures 5 , 6 , 7).…”
Section: Discussionmentioning
confidence: 99%
“…Alfalfa (Medicago sativa L.), known as the "Queen of Forages", is a globally cultivated forage crop valued for its high biomass yield and nutritional quality [16,17]. The change in its growth and development determines its yield and economic benefit [18]. Increasing biomass is a key breeding objective for alfalfa.…”
Section: Introductionmentioning
confidence: 99%